SPECIFICATION OF THE ECONOMIC CATEGORY OF THE SUSTAINABLE DEVELOPMENT - Łuszczyk, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
SummaryIn spite of an great interest in the paradigm of the sustainable development on the part of scientists and the society as a whole, it still appears troublesome to determine precisely the notion, not to say ultimate establishing the terminology being in force. It is also unsolved how to gain ways of implementing the new idea in the future development which without the broad agreement in ways of its fulfilling will stay in the sphere of deliberations of scientist.According to the author, fulfilling the sustainable development in its economic dimension can take place in conditions of the social market economy. The theoretical research carried out indicate high fitting contemporary interpretation of economic rules of Walter Eucken to principles determining the economic category of the sustainable development. This unanimity was also confirmed empirically. Countries, in which the economic system is closest to the ideal of the contemporary social market economy, they are achieving not only a good economic performance, but provide the highest quality of life for their societies.